Topical aspects of etiology and prevention of cervical cancer - M. Yu. Leshcheva; E. F. Astapenko; N. V. Gabbasova (Опухоли женской репродуктивной системы, 2022)
Cervical cancer (CC) occupies the fifth place in the structure of female oncopathology (n Russia. The share of CC is 5.2 % among all oncological diseases. iin Russia, 6.392 women died of CC in 2018. And the mortality rate from this disease is growing every year. In recent years, there has been an increase in the mortality rate among women aged 35 to 59 years at the age of the greatest social activity. The problem of etiology, pathogenesis and diagnosis of the disease remains relevant, despite the active development of medical science. The main cause of CC is considered to be the human papillomavirus of oncogenic genotypes. At the same time, even the active introduction of vaccination does not lead to a decrease in the rate of increase in morbidity and mortality from CC. At the same time, it is known that risk factors for the occurrence of the disease are early onset of sexual activity, frequent change of sexual partners, rejection of barrier methods of contraception, smoking, immunosuppression. Currently, the issue of the influence of sexually transmitted infections on the occurrence of CC has not been fully studied. We wondered what etiological factors have been most studied and reliably influence the occurrence of the disease, what preventive measures can help in this. We assume that only an integrated approach (lifestyle changes, vaccination, preventive medical examinations) can help defeat CC. The article discusses the key causes of the disease, the history of the study of the etiology of CC, the current state of the problem.